Major Selection Tendency among Creative Arts Students, Academy of Arts and Creative Technology, UMS † - Victor Pangayan (MDPI, 2022)
Both teachers and students are concerned about choosing majors. The gap between initial student expectations and external circumstances might lead to inferior academic performance and higher dropout rates. The purpose of this study was to determine the majors chosen by university freshmen and the factors that influenced their selection of creative arts majors. They filled out surveys about ASTiF’s Creative Arts majors. Results show that desire, family, lecturer, and course difficulty influence student major selection. According to the survey, students have their own perceptions of majors before pursuing these specialisations. Academic accomplishment, personal and social growth, and retention must be outlined in advance. Better preparation and communication between teachers, students, and parents are needed to identify more appropriate majors for each student. Universities could perhaps offer courses geared toward the aspects of academic choices, attitudes, and social skills. This should be a process, not an event, and should include peer-mentoring and staff—student engagement to choose an ASTiF Creative Arts major.